Renaissance papers 2012 - Shifflett, Andrew Eric, 1964-; Gieskes, Edward, 1968- (Renaissance papers, 2013)
Yearly volume of the best essays submitted to the Southeastern Renaissance Conference, focusing on sexuality in Elizabethan poetry, Renaissance drama and its links to the wider culture, and on seventeenth-century literature.